Indigenous Knowledge of Black Rice (Oryza sativa L. var. indica) in Central Aceh - Namira Hamim; Zumaidar Zumaidar; Saida Rasnovi; Risa Nursanty (Al-Kauniyah: Jurnal Biologi, 2022)
Abstract Black rice (Oryza sativa L. var. indica) is less available in the market than the usual white rice. Its availability is closely related to its utilization. One of the studies on the use of plants in certain tribes was obtained through ethnobotany. This study aimed to examine information regarding the use of black rice in Central Aceh. The methods used were Purposive Sampling and Participatory Rural Appraisal (PRA). This study involved 197 respondents of ethnic group; farmer, seller, and consumer of black rice, traditional healer. The results showed that black rice in Central Aceh was used by the community as medicine (72%) for gastritis, stomach acid, cholesterol, diabetes, thrush, fever, and as fertility booster; as food ingredients (10%) to make black rice tapai, gutel, and black rice crackers; as plant protectors (9%); as tools for traditional game (4%) called bebeulen; as cosmetic (3%) for smooth facial skin; and as animal feed (2%). Differences in regions indicated differences in recipes and habits of using certain plants.Abstrak Padi beras hitam (Oryza sativa L. var. indica) keberadaannya di pasaran sedikit dibandingkan dengan beras putih. Ketersediaan erat kaitannya dengan pemanfaatan. Salah satu kajian tentang pemanfaatan tumbuhan di suku tertentu diperoleh melalui etnobotani. Penelitian ini bertujuan untuk mengkaji informasi menyangkut pemanfaatan padi beras hitam di Kabupaten Aceh Tengah. Metode yang digunakan adalah Purposive Sampling dan Participatory Rural Appraisal (PRA). Pada penelitian ini melibatkan 197 responden yang terdiri dari kelompok adat; petani, penjual, dan pengguna beras hitam, serta tabib. Hasil penelitian menunjukkan bahwa padi beras hitam di Kabupaten Aceh Tengah dimanfaatkan oleh masyarakat sebagai obat-obatan (72%) yaitu untuk mengobati maag, asam lambung, kolesterol, diabetes, sariawan, demam, dan mudah memiliki keturunan, sebagai bahan pangan (10%) yaitu membuat tapai beras hitam, gutel, dan kerupuk nasi hitam, sebagai pelindung tanaman (9%), sebagai alat permainan (4%) yaitu bebeulen, serta sebagai bahan kosmetik (3%) yaitu menghaluskan wajah, dan sebagai pakan ternak (2%). Perbedaan daerah menunjukkan perbedaan resep dan kebiasaan penggunaan tumbuhan tertentu.